Case report: Experience of a rare case of rebound of the Kasabach-Merritt phenomenon during sirolimus treatment in kaposiform hemangioendothelioma - Liang Wang; Jing Li; Changhua Wu; Dan Song; Zhuang Liu; Yanli Niu; Jie Zhou; Lei Guo; Lei Guo; Lei Guo (Frontiers Media S.A., 2022)
Kaposiform hemangioendothelioma (KHE) is a rare vascular neoplasm associated with the Kasabach-Merritt phenomenon (KMP), which is a consumptive coagulopathy with associated potentially life-threatening thrombocytopenia. There are no standardized treatment protocols for the management of KHE with KMP. Moreover, there are limited reports regarding the treatment of cases of rebound. Herein, we describe a rare case of rebound of KHE/KMP, during systemic sirolimus treatment, successfully treated with embolization and vincristine infusion combined with microwave ablation.